On the identity of the generic name Iulidesmus Silvestri, 1895(Polydesmida: Paradoxosomatidae) - Hoffman, Richard L. (Zootaxa, 2012)
One of the most enigmatic of the early generic names impacting negatively on the taxonomy and nomenclature of Neotropical diplopods is Iulidesmus, proposed by Filippo Silvestri in 1895. The type species Iulidesmus typicus was based upon a female holotype, so that the structure of the male genitalia was (and remains) unknown for the species and genus.